The longitudinal relationships among adverse childhood experiences, lifestyle, and late-life depression: a latent growth mediation model - Cai, Xin; Yin, Haojie (Frontiers in Psychiatry, 2025)
BackgroundMany studies have shown that adverse childhood experiences (ACEs) are one of the causes of depressive symptoms in middle-aged and elderly individuals, but the combined impact of ACEs and lifestyle factors on depression has not been fully explored.MethodsThis study used data from the China Health and Retirement Longitudinal Study (CHARLS) from 2013, 2014, 2015, 2018, and 2020, including 10,835 middle-aged and elderly individuals. A latent variable growth curve model was used to analyze the trends of late-life depression and lifestyle changes. The mediating role of lifestyle in the relationship between ACEs and depression was also assessed.ResultsACEs were significantly associated with lower initial lifestyle levels (β = -0.138, P <.001) and higher depression severity (β = 0.253, P <.001). The mediation analysis results showed that the relationship between ACEs and the depression intercept was partially mediated by the initial level of lifestyle (β = 0.021, P <.001), and the relationship between ACEs and the depression slope was entirely mediated by the initial level of lifestyle (β = -0.010, P <.01). Different dimensions of ACEs had varying effects on depression.ConclusionsACEs are associated with the severity of depression, partly due to lower lifestyle levels. Interventions focused on reducing ACEs and improving lifestyle could effectively reduce the incidence of depression in middle-aged and elderly populations.